A Bourdieuian Reading of Sociology of Religion with Emphasis on Triple Concepts: Religious Field, Capital and Habitus - Behrouz Sepidnameh; Maghsoud Farasatkhah; Jabbar Rahmani (توسعه اجتماعی, 2019)
Religion is one of the oldest institutions of human beings that have the subject of study by various thinkers. The indeterminate nature of this concept (religion) has led to the plurality of its definitions and conceptualizations. The social aspect of the institution of religion has brought it the fore of sociologists' attention and Bourdieu is one of the sociologists who examined the evolution and development of religion through invention of concepts such as field, habitus, and capital. Bourdieu scatteredly has spoken about the sociology of religion in his articles and books. Accordingly, in this paper, it is attempted to present his ideas and notions on the sociological analysis of religion in a coherent and categorized way via documentary method. According to Bourdieu, market relations and rules dominate the field of religion. In this field, we see the roles of producer, supplier, consumer and salvation good. The actors in the field of religion struggle over obtaining religious capital and promote their status in the field of religion based on the amount of capital earned. The monopoly over the goods of salvation leads to the formation of a hierarchy system in the field of religion.